2019
DOI: 10.23889/ijpds.v4i1.461
|View full text |Cite
|
Sign up to set email alerts
|

Measuring multimorbidity in hospitalised patients using linked hospital episode data: comparison of two measures

Abstract: IntroductionMultimorbidity is a complex and growing health challenge. There is no accepted “gold standard” multimorbidity measure for hospital resource planning, and few studies have compared measures in hospitalised patients. AimTo evaluate operationalisation of two multimorbidity measures in routine hospital episode data in NHS Grampian, Scotland. MethodsLinked hospital episode data (Scottish Morbidity Record (SMR)) for the years 2009-2016 were used. Adults admitted to hospital as a general/acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…As a first step to understanding the implications of disease clusters, we aimed to identify and characterise multimorbidity clusters in a cohort of patients hospitalised in the Grampian region of Scotland. This builds on our previous work describing the overall extent of hospital multimorbidity 10 , 11 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As a first step to understanding the implications of disease clusters, we aimed to identify and characterise multimorbidity clusters in a cohort of patients hospitalised in the Grampian region of Scotland. This builds on our previous work describing the overall extent of hospital multimorbidity 10 , 11 .…”
Section: Introductionmentioning
confidence: 84%
“…The region consists of one large urban centre and is spread over approximately 3000 square miles of city, town, village and rural communities 14 . Full details have been previously published 10 , 11 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study comparing two multimorbidity measures reported that while 12 conditions were common to both measures, only 3 of these had identical ICD-10 codes. 11 All coding can be affected by variation in coding practices. In Scotland for instance, guidelines are provided regarding the coding of comorbidities, in which a list of comorbidity groups are prioritized as important conditions to record.…”
Section: Main Findingsmentioning
confidence: 99%
“…10 People with multimorbidity have more hospital admissions, stay longer in hospital, are more likely to be readmitted and have a higher risk of mortality than individuals without multimorbidity. 7,11 Patients with multimorbidity may be discharged from hospital with ongoing care needs, which can have an impact on their families and carers. 12 Identifying patients with multimorbidity at the point of admission has the potential for facilitating more informed care, taking account of the management of multiple conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation